Best Answer

2 - 6x = x - 2 is a simple equation that can be solved to find a value for x. This can be done as follows:

Move the terms that contain "x" to one side of the equation, and other terms to the opposite side:

2 - 6x = x - 2

2 + 2 = x + 6x

Now add the terms together:

4 = 7x

And divide both sides by seven to solve for x:

4/7 = x

So x is equal to four sevenths, or 0.571428 repeating.

Q: What is 2-6x equals x-2?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

(x2 + 26x +) : syntax error.x2 + 26x

38 = 26x - 7x 38 = 19x (38/19) = x 2 = x

.740

x2+26x = 68 Completing the square: (x+13)2-169-68 = 0 (x+13)2-237 = 0 x+13 = -/+ sq rt 237 x = -13-/+ sq rt 237

26x = 156 Divide both sides of the equation by 26 to find the value of x: x = 6

Related questions

(x2 + 26x +) : syntax error.x2 + 26x

x2+26x = 68 x2+26x-68 = 0 (x+13)2-68 = 0 (x+13)2-169-68 = 0 x+13 = +/- the square root of 237 x = -13 +/- the square root of 237

x2 + 26x + 48 = (x + 24)(x + 2)

x2+36x+120 (x+6)(x+20)

26x-4 = 25 +4 +4 26x = 29 x= 29/26 or 1.115...

38 = 26x - 7x 38 = 19x (38/19) = x 2 = x

.740

x2+26x = 68 Completing the square: (x+13)2-169-68 = 0 (x+13)2-237 = 0 x+13 = -/+ sq rt 237 x = -13-/+ sq rt 237

26x = 156 Divide both sides of the equation by 26 to find the value of x: x = 6

2x4 - 26x2 + 72 = 0Divide each side by 2:x4 - 13x2 + 36 = 0(x2 - 9) (x2 - 4) = 0A). x2 - 9 = 0B). x2 - 4 = 0______________________A). (x + 3) (x - 3) = 0x = +3x = -3B). (x + 4) (x - 4) = 0x = +4x = -4

26x + 9 = 699Subtract 9 from each side:26x = 690Divide each side by 26 :x = 690/26 = 26 and 14/690 = 26 and 7/345 = 26.5385 (rounded)

x2 + x2 = 2x2